2019
DOI: 10.1002/glia.23726
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of inflammatory diseases of the nervous system: Human disease versus animal models

Abstract: Numerous recent studies have been performed to elucidate the function of microglia, macrophages, and astrocytes in inflammatory diseases of the central nervous system. Regarding myeloid cells a core pattern of activation has been identified, starting with the activation of resident homeostatic microglia followed by recruitment of blood borne myeloid cells. An initial state of proinflammatory activation is at later stages followed by a shift toward an‐anti‐inflammatory and repair promoting phenotype. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 157 publications
1
34
0
Order By: Relevance
“…The present study reports for the first time that spheroids may also retain damaged mitochondria. This could be a key fact in PD where the release of damaged mitochondria may activate neuro‐inflammation (Healy, Yaqubi, Ludwin, & Antel, 2020; Joshi et al, 2019; Lassmann, 2020; Maeda & Fadeel, 2014; Matheoud et al, 2016; Wilkins et al, 2017; Q. Q. Yang & Zhou, 2019; Zhang et al, 2010) and accelerate the DAn degeneration (Chung et al, 2010; Yan et al, 2014). The retention of damaged mitochondria in spheroids could explain why the selective degeneration of DAergic terminals which is accompanied by the production of spheroids does not activate neuro‐inflammation (Morales et al, 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The present study reports for the first time that spheroids may also retain damaged mitochondria. This could be a key fact in PD where the release of damaged mitochondria may activate neuro‐inflammation (Healy, Yaqubi, Ludwin, & Antel, 2020; Joshi et al, 2019; Lassmann, 2020; Maeda & Fadeel, 2014; Matheoud et al, 2016; Wilkins et al, 2017; Q. Q. Yang & Zhou, 2019; Zhang et al, 2010) and accelerate the DAn degeneration (Chung et al, 2010; Yan et al, 2014). The retention of damaged mitochondria in spheroids could explain why the selective degeneration of DAergic terminals which is accompanied by the production of spheroids does not activate neuro‐inflammation (Morales et al, 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Even in the normal appearing white matter of MS patients there are nodules of activated microglia, but whether these microglia are homeostatic or activated is debatable since one study showed a loss of P2RY12 but another showed unaltered P2RY12 gene expression (16,33). The significance of these nodules of activated microglia remains unclear since they either represent the earliest stage of MS or the by-product of Wallerian degeneration from an upstream lesion (14). The regional heterogeneity of microglia, which had originally been reported in mice, was also found to have a disease specific manifestation in progressive MS patients who demonstrate an upregulation of genes involved in lipid processing in normal appearing white matter and iron homeostasis in normal appearing gray matter (16,36).…”
Section: Microglia and Ms Pathogenesismentioning
confidence: 99%
“…Cell surface markers including transmembrane protein 119 (TMEM119) and purinergic receptor P2Y12 are emerging as more reliable markers of microglial state under pathological conditions (12,13). The previously favored dichotomy of proinflammatory (M1) and anti-inflammatory (M2) microglia is no longer considered valid since evidence now indicates that microglial phenotypes are transient and demonstrate temporal and spatial evolution (1,11,14). An intriguing new phenotype, deemed "dark microglia, " has also been discovered that may play a role in pathological remodeling of neuronal circuits (15).…”
Section: Introduction: Microglia In Development and Disease Statesmentioning
confidence: 99%
“…Peripheral inflammation has been demonstrated to be a trigger for microglial activation and sickness behavior in humans and animals [4,5]. In addition, astrocytes, abundant glial cells that constitute approximately 40% of brain cells, participate in homeostasis in the healthy CNS and neuropathogenesis induced by CNS injury or peripheral inflammation [6,7]. The two glial cell types are also involved in metabolic disorder-linked neuroinflammation [8].…”
Section: Introductionmentioning
confidence: 99%